Derivatives, pricing efficiency and gharar: evidence on embedded options in Malaysia - Haron, Razali (IIUM Institute of Islamic Banking and Finance, 2014)
Derivatives, despites their extensive usage as risk management tools, receive differing arguments among the Muslim scholars. Focusing on embedded option contracts, the resolution of Islamic Fiqh Academy, Jeddah No (63/1/7) under the financial markets considers the currently applied option contracts as different from the Shariah nominated contracts and being neither a sum of money nor a utility or a financial right which may be waived, makes it forbidden in Shariah. Most Islamic scholars accuse option contracts of containing gharar and are transacted for speculative gains thus, prohibited in fiqh muamalat. Therefore, this study intends to investigate the accusation of the gharar elements in the option contracts. The Black Scholes Option Pricing Model (BSOPM) is used to examine the pricing of 183 outstanding embedded options (equity warrants) from January 2006 to December 2012. Cases of mispricing were detected in reference with their theoretical values indicating inefficiency in the Malaysian market and speculative activities taken place which are prohibited in Islam. Speculation contains gharar (uncertainty) and leads to maysir (gambling) and may result in wealth accumulation at the expense of other parties’ jahl (ignorance). Violating the concept of adl (justice), not serving the concept of maslahah (public interest) and not complying with the Maqasid al Shariah make speculation forbidden. The existence of gharar is empirically and statistically evidenced in the speculation activities indicated by the excessive mispricing detected in this study. This study contributes significantly in the literature by providing empirical evidence which is very much lacking in the study of options in Islamic Finance.